Range of Motion Outcomes Post Cruciate-Retaining vs Posterior Stabilized Total Knee Arthroplasty: A Retrospective Multi-Centre Cohort Study - Oliver Emmanuel Yausep; Ifran Saleh; Adryan Tanujaya (Indonesian Hip and Knee Society (IHKS), 2021)
Background: The outcome for TKA (total knee arthroplasty) upon whether the posterior cruciate ligament is preserved with cruciate retaining (CR) prostheses or sacrificed with posterior stabilized (PS) prostheses are still debated between studies. Materials and Methods: We included a total of 144 knees operated with cemented fixed bearing primary CR or PS TKAs. Independent t-tests were conducted for the outcomes and possible confounding variables between groups where relevant, with analyses using Chi-squared tests for nominal data. Results: Operation on patients with age of lower than 65 years predicts increased intraoperative bleeding volume (p = 0.037), pre-operative range of motion (ROM) of less than 90 degrees was a predictor for better improved post-operative ROM (p 0.001) and PS prostheses is superior to CR in terms of ROM improvement (p = 0.04), however with both groups achieving similar maximum ROM (p = 0.308). Conclusion: Improvement of ROM is increased by the use of PS prostheses compared to CS prostheses, with pre-operative ROM as a possible confounding factor and the maximum ROM achieved for both prostheses being similar. Lower age of the operation is also related to increased intraoperative bleeding